Reduced Graphene Oxide Nanohybrid–Assembled Microneedles as Mini‐Invasive Electrodes for Real‐Time Transdermal Biosensing. Issue 6 (3rd January 2019) - Jin, Quanchang; Chen, Hui‐Jiuan; Li, Xiangling; Huang, Xinshuo; Wu, Qianni; He, Gen; Hang, Tian; Yang, Chengduan; Jiang, Zhen; Li, Enlai; Zhang, Aihua; Lin, Zhihong; et al.
Abstract: A variety of nanomaterial‐based biosensors have been developed to sensitively detect biomolecules in vitro, yet limited success has been achieved in real‐time sensing in vivo. The application of microneedles (MN) may offer a solution for painless and minimally‐invasive transdermal biosensing. However, integration of nanostructural materials on microneedle surface as transdermal electrodes remains challenging in applications. Here, a transdermal H2 O2 electrochemical biosensor based on MNs integrated with nanohybrid consisting of reduced graphene oxide and Pt nanoparticles (Pt/rGO) is developed. The Pt/rGO significantly improves the detection sensitivity of the MN electrode, while the MNs are utilized as a painless transdermal tool to access the in vivo environment. The Pt/rGO nanostructures are protected by a water‐soluble polymer layer to avoid mechanical destruction during the MN skin insertion process. The polymer layer can readily be dissolved by the interstitial fluid and exposes the Pt/rGO on MNs for biosensing in vivo. The applications of the Pt/rGO‐integrated MNs for in situ and real‐time sensing of H2 O2 in vivo are demonstrated both on pigskin and living mice. This work offers a unique real‐time transdermal biosensing system, which is a promising tool for sensing in vivo with high sensitivity but in a minimally‐invasive manner. Abstract : Transdermal H2 O2 electrochemical biosensors based on microneedles (MNs) integrated with nanohybrid consisting of reduced graphene oxide and Pt nanoparticles (Pt/rGO) are developed. The polyvinylpyrrolidone‐protected Pt/rGO significantly improves the detection sensitivity of the MN electrode, while the MNs are utilized as a painless transdermal tool to access the in vivo environment.